1988
DOI: 10.1037/0022-006x.56.6.903
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive attributes of depression in children and adolescents.

Abstract: This study explores whether cognitive attributes differentiate depressed children from those with other psychiatric disorders. The subjects were 108 children from 7 to 17 years of age. Forty-seven children were diagnosed as currently depressed, 30 as having had an episode of major depression within the last year (depressed-resolved), and 31 with diagnoses other than depression (nondepressed). The subjects completed the Piers-Harris Children's Self-Concept Scale, the Children's Hopelessness Scale, the Nowicki-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
11

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(60 citation statements)
references
References 26 publications
4
43
0
11
Order By: Relevance
“…Proponents of this viewpoint have argued that negative self-perceptions are symptoms of, rather than contributors to, depression. At least four studies have found that clinically depressed children's and adolescents' self-perceptions improve as their depressive symptoms remit (Asarnow & Bates, 1988;Gotlib, Lewinsohn, Seeley, Rohde, & Redner, 1993;McCauley et al, 1988;Tems, Stewart, Skinner, Hughes, & Emslie, 1993). These findings suggest that a negative self-perception may be a state-dependent symptom of depression rather than a stable characteristic of depressed children.…”
Section: Negative Self-perceptionsmentioning
confidence: 71%
See 1 more Smart Citation
“…Proponents of this viewpoint have argued that negative self-perceptions are symptoms of, rather than contributors to, depression. At least four studies have found that clinically depressed children's and adolescents' self-perceptions improve as their depressive symptoms remit (Asarnow & Bates, 1988;Gotlib, Lewinsohn, Seeley, Rohde, & Redner, 1993;McCauley et al, 1988;Tems, Stewart, Skinner, Hughes, & Emslie, 1993). These findings suggest that a negative self-perception may be a state-dependent symptom of depression rather than a stable characteristic of depressed children.…”
Section: Negative Self-perceptionsmentioning
confidence: 71%
“…Evidence suggests that depressed children are unhappy with themselves and hold negative expectations about the future (e.g., Asarnow & Bates, 1988;McCauley, Mitchell, Burke, & Moss, 1988), do not believe they can solve their problems (Weisz, Sweeney, Proffitt, & Carr, 1993), and are critical of their academic and social competence (see Hammen, 1990;Hammen & Rudolph, 1996, for reviews). However, there is disagreement in the childhood depression literature as to whether negative self-perceptions may lead to depression or whether depression causes a negative view of the self (Garber et al, 1990).…”
Section: Negative Self-perceptionsmentioning
confidence: 99%
“…Similarly, among clinical samples some studies have found differences in cognitive style between youth with depression diagnoses compared to those with other diagnoses (Kaslow, Rehm, Pollock, & Siegel, 1988;McCauley, Mitchell, Burke, & Moss, 1988). There also appears to be some specificity of automatic thought content depending on symptomatology, with thoughts of personal failure associated with depression and thoughts of hostility associated with externalizing symptoms (Schniering & Rapee, 2004).…”
Section: Specificity Of Cognitive Vulnerability For Depressionmentioning
confidence: 99%
“…In Haley et al [1985], Kazdin [1987], and Saylor et al [1984], diagnoses were assigned without the use of a formal structured interview. In contrast, Hodges [1990], McCauley et al [1988], and Timbremont et al [2004] used structured interviews to determine diagnostic status. Consequently, the reliability of the diagnostic groups likely varies across these studies.…”
mentioning
confidence: 96%
“…Less clear, however, is the CDI's ability to distinguish between children with depressive disorders and children who display other kinds of clinical problems [for a review, see Silverman and Rabian, 1999]. Some studies have found that children with depressive disorders score significantly higher on the CDI than nondepressed clinical samples [e.g., Haley et al, 1985;Hodges, 1990;McCauley et al, 1988; whereas other studies have reported no differences between the CDI scores of depressed and nondepressed clinical samples [e.g., Kazdin, 1987;Kazdin et al, 1983;Saylor et al, 1984].…”
mentioning
confidence: 97%